C-MAC videolaryngoscope compared with direct laryngoscopy for rapid sequence intubation in an emergency department: A randomised clinical trial. Issue 12 (December 2016) - Sulser, Simon; Ubmann, Dirk; Schlaepfer, Martin; Brueesch, Martin; Goliasch, Georg; Seifert, Burkhardt; Spahn, Donat R.; Ruetzler, Kurt
Abstract : BACKGROUND: Airway management in the emergency room can be challenging when patients suffer from life-threatening conditions. Mental stress, ignorance of the patient's medical history, potential cervical injury or immobilisation and the presence of vomit and/or blood may also contribute to a difficult airway. Videolaryngoscopes have been introduced into clinical practice to visualise the airway and ultimately increase the success rate of airway management. OBJECTIVE: The aim of this study was to test the hypothesis that the C-MAC videolaryngoscope improves first-attempt intubation success rate compared with direct laryngoscopy in patients undergoing emergency rapid sequence intubation in the emergency room setting. DESIGN: A randomised clinical trial. SETTING: Emergency Department of the University Hospital, Zurich, Switzerland. PATIENTS: With approval of the local ethics committee, we prospectively enrolled 150 patients between 18 and 99 years of age requiring emergency rapid sequence intubation in the emergency room of the University Hospital Zurich. Patients were randomised (1 : 1) to undergo tracheal intubation using the C-MAC videolaryngoscope or by direct laryngoscopy. INTERVENTIONS: Owing to ethical considerations, patients who had sustained maxillo-facial trauma, immobilised cervical spine, known difficult airway or ongoing cardiopulmonary resuscitation were excluded from our study. All intubations were performed by one of three very experienced anaesthesia consultants. MAIN OUTCOME MEASURES: First-attempt success rate served as our primary outcome parameter. Secondary outcome parameters were time to intubation; total number of intubation attempts; Cormack and Lehane score; inadvertent oesophageal intubation; ease of intubation; complications including violations of the teeth, injury/bleeding of the larynx/pharynx and aspiration/regurgitation of gastric contents; necessity of using further alternative airway devices for successful intubation; maximum decrease of oxygen saturation and technical problems with the device. RESULTS: A total of 150 patients were enrolled, but three patients had to be excluded from the analysis, resulting in 74 patients in the C-MAC videolaryngoscopy group and 73 patients in the direct laryngoscopy group. Tracheal intubation was achieved successfully at the first attempt in 73 of 74 patients in the C-MAC group and all patients in the direct laryngoscopy group ( P  = 1.0). Time to intubation was similar (32 ± 11 vs. 31 ± 9 s, P  = 0.51) in both groups. Visualisation of the vocal cords, represented as the Cormack and Lehane score, was significantly better using the C-MAC videolaryngoscope ( P  < 0.001). CONCLUSION: Our study demonstrates that visualisation of the vocal cords was improved by using the C-MAC videolaryngoscope compared with direct laryngoscopy. Better visualisation did not improve first-attempt success rate, which in turn was probably based on the high level of experience of the participating anaesthesia consultants. TRIAL REGISTRATION: Clinicaltrials.gov identifier NCT02297113.